Governing cyberspace : behavior, power, and diplomacy - Broeders, D. (Dennis); Berg, Bibi van den (Digital Technologies and Global Politics, 2020)
Cyber norms and other ways to regulate responsible state behavior in cyberspace is a fast-moving political and diplomatic field. The academic study of these processes is varied and interdisciplinary, but much of the literature has been organized according to discipline. Seeking to cross disciplinary boundaries, this timely book brings together researchers in fields ranging from international law, international relations, and political science to business studies and philosophy to explore the theme of responsible state behavior in cyberspace. . Divided into three parts, Governing Cyberspace first looks at current debates in and about international law and diplomacy in cyberspace. How does international law regulate state behaviour and what are its limits? How do cyber superpowers like China and Russia shape their foreign policy in relation to cyberspace? The second focuses on power and governance. What is the role for international organisations like NATO or for substate actors like intelligence agencies? How do they adapt to the realities of cyberspace and digital conflict? How does the classic balance of power play out in cyberspace and how do different states position themselves? The third part takes a critical look at multistakeholder and corporate diplomacy. How do global tech companies shape their role as norm entrepreneurs in cyberspace, and how do their cyber diplomatic efforts relate to their corporate identity?